The Eco-Friendly Culture of the Rajbanshis of North Eastern India and Their use of Banana and its Plant - Mandal, Wg Cdr Ranjit Kumar (Journal of Advanced Research in Humanities and Social Sciences, 2020)
The human society has undergone a drastic change in the recent time due to rapid industrialization and globalization. The people have shifted largely from the eco friendly living to the living habits that dependents largely on industrial products. Whereas, there are some communities like that of the Rajbanshis in the North Eastern India which are still maintaining the nature friendly living style even these days. But it is a matter of a great concern that the consumerism is creeping into the nooks and corners of India and the social values are changing rapidly. The objective of the article is to record some of such ecofriendly values of the Rajbanshi community of North Eastern India which had contributed to the healthy living of the past generations. This is an account of the fact which the author has seen himself sine the middle of the previous century, though it is changing day by day. How to cite this article: Mandal RK. The Eco-Friendly Culture of the Rajbanshis of North Eastern India and Their use of Banana And its Plant. J Adv Res Humani Social Sci 2020; 7(1): 22-30. Orcid Id: https://orcid.org/0000-0001-7215-4648